Analisis Perilaku Komsumtif Remaja Terkait Adanya Diskon pada E-Commerce Shopee sebagai Motivasi Belanja Online - Yuliana; Abd Aziz; Waqi’atul Aqidah (Jurnal Informatika Ekonomi Bisnis, 2024)
This research aims to describe the reasons why teenagers have consumptive behavior related to discounts on Shopee e-commerce as motivation for online shopping, describe the factors that influence teenagers to behave consumptively related to discounts on Shopee e-commerce as online shopping motivation and describe ways to reduce teenagers' consumptive behavior. regarding discounts on E-Commerce Shopee as motivation for online shopping. This type of research is qualitative research with a case study design. The subjects in this research focused on teenagers in Seneng Village. The location of this research was in Seneng Village, Krucil District. The data collection techniques used were in-depth interviews, observation and documentation. The results of the research show that the reasons for adolescent consumptive behavior related to discounts on the E-Commerce Shoppe as motivation for online shopping include: personal needs and the influence of friends, factors that influence adolescent consumptive behavior related to discounts on the E-Commerce Shoppe as motivation for online shopping are influenced by: flash sales Big discounts or twin dates and free shipping vouchers, the way to reduce teenagers' consumptive behavior regarding discounts on Shopee E-Commerce as a motivation for online shopping is by having the intention to save money and prioritizing spending.